2019
DOI: 10.1021/acs.chemrev.9b00048
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photochemical Reduction and Functionalization Chemistry of the Uranyl Dication, [UVIO2]2+

Abstract: The uranyl ion, [UVIO2]2+, possesses rigorously trans, strongly covalent, and chemically robust U-oxo groups. However, through the use of anaerobic reaction techniques, both one- and two-electron reductive functionalization of the uranyl oxo groups has been discovered and developed. Prior to 2010, this unusual reactivity centered around the reductive silylation of the uranyl ion which entailed conversion of the oxo ligands into siloxy ligands and reductive metalation of the uranyl oxo with Group 1 and f-block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 127 publications
7
121
0
Order By: Relevance
“…The computational study also revealed that the U(IV) and Pu(IV) complexes have more covalent character in their bonding than that found with the other metal ions; [CeL2] showed increased covalent behavior compared to [ThL2]. Schiff bases have also played an important role in the reduction and functionalization chemistry of {U VI O2} 2+ [9]. As mentioned in Section 3, the uranyl(VI) dication is thermodynamically stable and rather inert to chemical functionalization in the normal laboratory atmosphere.…”
Section: Scientific Interest In the Chemistry Of Actinoid-schiff Basementioning
confidence: 94%
See 1 more Smart Citation
“…The computational study also revealed that the U(IV) and Pu(IV) complexes have more covalent character in their bonding than that found with the other metal ions; [CeL2] showed increased covalent behavior compared to [ThL2]. Schiff bases have also played an important role in the reduction and functionalization chemistry of {U VI O2} 2+ [9]. As mentioned in Section 3, the uranyl(VI) dication is thermodynamically stable and rather inert to chemical functionalization in the normal laboratory atmosphere.…”
Section: Scientific Interest In the Chemistry Of Actinoid-schiff Basementioning
confidence: 94%
“…As far as we are aware, this is a first attempt to summarize and discuss the synthetic and structural chemistry, the properties and the potential applications of dinuclear and oligonuclear An complexes based on Schiff-based ligands. The topic has been partly covered in some older, excellent reviews or book chapters dealing with the chemistry of actinoids [2][3][4][5][6][7][8][9][10] and the coordination chemistry of Schiff bases [11].…”
Section: Scope and Organization Of This Reviewmentioning
confidence: 99%
“…The need for a better understanding of the mechanism of the environmental reduction of uranyl(VI) to uranium(IV), which is key for the development of remediation strategies, has spurred numerous studies of the reduction and functionalization of uranyl species both in the gas phase and in non‐aqueous anaerobic media . Significant progress has been made in recent years in the development of systems that allowed the reduction of uranyl(VI) to uranyl(V) .…”
Section: Methodsmentioning
confidence: 99%
“…The need for a better understanding of the mechanism of the environmental reduction of uranyl(VI) to uranium(IV), which is key for the development of remediation strategies, has spurred numerous studies of the reduction and functionalization of uranyl species both in the gas phase and in non‐aqueous anaerobic media . Significant progress has been made in recent years in the development of systems that allowed the reduction of uranyl(VI) to uranyl(V) . In contrast, fewer examples of controlled reduction of uranyl(VI) and uranyl(V) complexes to well‐defined U IV compounds have been reported and they all require the preliminary functionalization of the two uranyl oxo ligands with Lewis acids or metal cations…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation